Intra‐articular nuclear factor‐κB blockade ameliorates collagen‐induced arthritis in mice by eliciting regulatory T cells and macrophages. (10th April 2013) - Min, S.‐Y.; Yan, M.; Du, Y.; Wu, T.; Khobahy, E.; Kwon, S.‐R.; Taneja, V.; Bashmakov, A.; Nukala, S.; Ye, Y.; Orme, J.; Sajitharan, D.; et al.
Summary Nuclear factor (NF)‐κB is a transcription factor implicated in the pathogenesis of autoimmune disorders such as rheumatoid arthritis (RA). Here we have examined the effect of intra‐articular administration of the IKK inhibitor, NEMO‐binding domain peptide (NBD), on the severity of collagen‐induced arthritis (CIA). NBD peptides were injected intra‐articularly into the knee joints of DBA/1J mice after the onset of disease. Collagen‐injected mice given a scrambled peptide served as controls. Arthritis severity was determined by visual examination of paws. Intra‐articular NBD injection reduced the arthritis score and ameliorated morphological signs of bone destruction compared to the controls. Serum levels of type‐II collagen‐specific immunoglobulin (Ig)G2a antibodies were lower in NBD‐treated mice versus the control mice, whereas the levels of type‐II collagen‐specific IgG1 antibodies were increased by NBD treatment. NBD treatment diminished the proinflammatory cytokines interleukin (IL)‐17 and interferon (IFN)‐γ in serum, but increased the regulatory cytokine IL‐10. NBD‐treated CIA mice exhibited significantly higher percentages and numbers of forkhead box protein 3 (FoxP3+)CD4+CD25+ regulatory T cells than controls. Immunofluorescence analysis of NBD‐treated mice revealed that FoxP3 and Ym1, a marker of alternatively activated macrophages, were juxtaposed to each other within draining inguinal lymph nodes. Intra‐articular administration of NBD peptide is effective as an experimental therapy in a murine model of RA. Nevertheless, the intra‐articular treatment modality is still associated with systemic effects on the immune system.